The Relationship between Nurse Attitudes and Family Support in the Care of Elderly Patients with Chronic Illnesses - Putri, Suraya; Rachmah, Rachmah; Rahmawati, Rahmawati (Indonesian Journal of Global Health Research, 2024)
Elderly care for patients with chronic illnesses has become a critical issue in Indonesia, given the high prevalence of chronic conditions among the elderly, such as diabetes, hypertension, and heart disease. Positive nurse attitudes and family support play essential roles in enhancing the quality of care and well-being of elderly patients. This study analyzes the relationship between nurse attitudes and family support in the quality of care provided to elderly patients with chronic illnesses. The research employed a quantitative approach with an observational cross-sectional design, involving 50 elderly participants selected through purposive sampling. The results indicate that patients receiving care from nurses with positive attitudes and strong family support tend to experience a higher quality of care (p < 0.05). Empathetic nurse attitudes and consistent family support improve patient comfort, adherence to treatment, and clinical outcomes. These findings highlight the importance of synergy between positive nurse attitudes and family support in optimizing elderly care and reducing the potential for loneliness and mental health decline among patients.